Macro Effects of Corporate Restructuring in Japan - Kim, Se-Jik. (Washington, D.C. : International Monetary Fund, 2003)
This paper presents a framework for quantitatively evaluating the macroeconomic effects of corporate restructuring and applies it to Japan. Using firm-level financial statement data, it estimates total factor productivity (TFP) of individual Japanese firms. Given the estimated distribution of productivity across firms, the paper simulates the effect of optimal restructuring, that is, reallocation of resources from less-productive firms to more-productive ones, on the dynamic path of aggregate output. The results show that the benefits of restructuring could substantially exceed the costs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet